Strategi Guru dalam Meningkatkan Keterampilan Literasi Membaca Siswa melalui Media Digital Interaktif di Madrasah Ibtidaiyah - Shahzadi Hina Sain; Haris Suwondo (Insan Zenius Ilmiah, 2026)
This study is a qualitative study using a library research approach, which is included in the literary research category. This method is carried out through reading, taking notes, synthesizing, and analyzing various relevant library sources, such as books, scientific journals, articles, and other documents. The focus of this study is to examine teachers' strategies in improving the reading literacy of elementary madrasah students through the use of interactive digital media. The results of the literature review indicate that the use of digital media such as audiovisual e-books, educational videos, and game-based applications can significantly increase students' interest, motivation, and reading skills. The role of teachers as facilitators and designers of adaptive learning is a key factor in the success of this digital media integration. This study also emphasizes the importance of teachers' digital literacy competencies, infrastructure readiness, and content suitability with Islamic values ​​and the local context. These findings reinforce the theories of social constructivism and multimedia learning, which emphasize the importance of social interaction and multisensory stimulation in the learning process. However, challenges such as the digital divide still need to be addressed through ongoing training and collaboration between stakeholders. The implications of this research point to an inclusive and sustainable digital learning transformation, with teachers as the main agents of change in building a contextual and valuable digital literacy culture in madrasas